Solve the following system:{12 x = 54 - 6 y | (equation 1)-17 x = -6 y - 62 | (equation 2)
Express the system in standard form:{12 x + 6 y = 54 | (equation 1)-(17 x) + 6 y = -62 | (equation 2)
Swap equation 1 with equation 2:{-(17 x) + 6 y = -62 | (equation 1)12 x + 6 y = 54 | (equation 2)
Add 12/17 × (equation 1) to equation 2:{-(17 x) + 6 y = -62 | (equation 1)0 x+(174 y)/17 = 174/17 | (equation 2)
Multiply equation 2 by 17/174:{-(17 x) + 6 y = -62 | (equation 1)0 x+y = 1 | (equation 2)
Subtract 6 × (equation 2) from equation 1:{-(17 x)+0 y = -68 | (equation 1)0 x+y = 1 | (equation 2)
Divide equation 1 by -17:{x+0 y = 4 | (equation 1)0 x+y = 1 | (equation 2)
Collect results:Answer: {x = 4 {y = 1
Please note the { are supposed to span over both equations but it interfaces doesn't allow it. Please see attachment for clarification.
Answer:
this might help better
Step-by-step explanation:
5√24
=10√6(Decimal: 24.494897)
Answer:
3.37
Step-by-step explanation:
I am not very sure but this would be the answer.
X-x-2/6=x-7/3+2/3
-2/6+7/3-2/3=x
x= -2/6+5/3
x= 8/6
x= 4/3
Mid point of x:
{2-(-6)} : 2
8 : 2
4
mid point of y:
(5-3) : 2
2 : 2
1
so (4,1)